Ihdad Bagi Suami dalam Kompilasi Hukum Islam Perspektif Maqasid Al-Shariah - Moch. Nurcholis (FALASIFA : Jurnal Studi Keislaman, 2017)
The books of fiqh discussed the concept of ih}da>d applies only to the wife who was left to die by her husband with the same period `iddah death, i.e. four (4) months in ten (10) days. It is inversely proportional to the concept of ih}da>d that apply in Article 170 paragraph (2) the Compilation of Islamic Law (KHI) which establishes the obligation of mourning for her husband who was left to die by his wife with time according to propriety. Following the truth of the theory in coherence (the truth on the basis of the consistency argument), then in Article 170 paragraph (2) is provision to the same as subsection (1), i.e. ih}da>d both make law had to be done, even though Â by the wife and husband. The differences concept ,the researchers eventually focused on two aspects of the problem, namely: (1) What is the reason of shar`iy used in the determination of the ih}da>d for husband in Article 170 paragraph (2) the Compilation of Islamic Law (KHI)?, (2) How perspective maqa>s}id al-shari>â€™ah to the ih}da>d for husband in the Article 170 paragraph (2) the Compilation of Islamic Law (KHI)?. The researcher of this articel belongs to the normativeÂ research. While the views from the data collection which has been examined, the research belongs to library research (study library). Primary and Secondary data were analyzed by using descriptive analytic method, that describes the whole theory about maqa>s}id al-shari>`ah which used to analyze the datas of the husband who has ih}da>d. While the approach in analyzing the data by using a statutory approach (statute approach). There are two research results. The first, shar`iy used to determine of the ih}da>d for husband in Article 170 paragraph (2) the Compilation of Islamic Law (KHI) are the norms of Islamic law, both rule in us}uliyah or the rule of fiqhiyah. The second, ih}da>d for the husband in Article 170 paragraph (2) the Compilation of Islamic Law (KHI) in the perspective of maqa>s}id al-shari>`ah has been in accordance with universal values of shara` is jalb al-mas}a>lih wa darâ€™ al-mafa>sid (brought good and resist damage). The category of maqa>s}id, the provisions of this article are included in the categories of al-d{aru>riyya>t, especially hifz al-â€˜ird i.e. the imposition of religious law in order to guarantee and maintain the honor. Â Keywords: Ih}da>d, Compilation of Islamic Law (KHI), Maqa>s}id al-Shari>`ah.